2022
DOI: 10.3389/fimmu.2022.1002551
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of extracellular vesicle-mediated immune evasion in melanoma

Lothar C. Dieterich

Abstract: Melanoma-derived extracellular vesicles (EVs) have been found to promote tumor growth and progression, and to predict patient responsiveness to immunotherapy. Consequently, EVs have been implicated in tumor immune evasion, and multiple studies reported immune-regulatory activities of melanoma EVs in vitro and in vivo. This review highlights mechanistic insights in EV-mediated regulation of various immune cell types, including effects on inflammatory, apoptotic, stress-sensing and immune checkpoint pathways as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…CD27-expressing MPs supplied by the transfusion of platelet concentrates could, therefore, be involved in the failure of anti-CD27 immunotherapy. The mechanism of action of MPs has not yet been determined ( 28 34 ), but we suggest that MPs present in transfusion products may compete with cellular targets. We tested this hypothesis by performing assays of in vitro competition between MPs and cells ( Figure 6 ), with the same ratios of CD27-expressing MPs to cells as above.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…CD27-expressing MPs supplied by the transfusion of platelet concentrates could, therefore, be involved in the failure of anti-CD27 immunotherapy. The mechanism of action of MPs has not yet been determined ( 28 34 ), but we suggest that MPs present in transfusion products may compete with cellular targets. We tested this hypothesis by performing assays of in vitro competition between MPs and cells ( Figure 6 ), with the same ratios of CD27-expressing MPs to cells as above.…”
Section: Resultsmentioning
confidence: 86%
“…It has been suggested that MPs are involved in resistance to anti-PD1 immunotherapies ( 28 34 ). CD27-expressing MPs supplied by the transfusion of platelet concentrates could, therefore, be involved in the failure of anti-CD27 immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[63] The exploration of EVs' pathological role, their use as biomarkers in clinical diagnosis, and their involvement in disease treatment, initially began in the field of cancer, yielding exciting results. [62][63][64] For example, in melanoma, EVs secreted by cancer cells inhibit the maturation of dendritic cells and the production of cytokines, [65] while EVs derived from glioma cells can decrease the local Tregs content, thus mediating immunosuppression. The combination and content of non-coding RNA (ncRNA) in EVs derived from tumor cells are often specific, giving them potential as disease diagnosis biomarkers, such as miR-21, miR-221, miR301a in glioma, [66] and miR-25, miR-222, miR-16, miR324-3p in breast cancer.…”
Section: Evsmentioning
confidence: 99%
“…Wieckowski et al demonstrated that tumor-derived sEVs carry Fas-L protein, which contributes to TME immune suppression by promoting Treg proliferation and CD8 + T cell apoptosis [ 119 , 120 ]. HSP72 and HSP105 in sEVs in the sera of melanoma, lung cancer and BC patients activate dendritic cells and trigger IL-6 production, which promote tumor invasion by increasing MMP9 expression [ 121 ].…”
Section: Tumor-derived Sevs Play Vital Roles In the Bc Microenvironmentmentioning
confidence: 99%